A composite substrate based on aluminum nitride ceramic material and a method for producing and using the same
By constructing a composite substrate on an AlN ceramic substrate and utilizing lateral epitaxial technology with patterned structures and polycrystalline coatings, the challenge of growing GaN or AlN single crystals on AlN ceramic materials has been solved, achieving high-efficiency, low-cost, and high-quality epitaxial growth suitable for 5G and HEMT devices.
Patent Information
- Application Number
- CN202010590343.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-06-24
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2040-06-24
AI Technical Summary
Existing technologies make it difficult to achieve epitaxial growth of GaN or AlN single crystals on amorphous or polycrystalline AlN ceramic materials, and traditional substrate materials are expensive and cannot meet the requirements of high-power and high-mobility GaN-based devices.
A composite substrate based on AlN ceramic material is used, including an aluminum nitride ceramic substrate, a patterned structure layer and a polycrystalline coating layer. GaN or AlN single crystals are grown by lateral epitaxy, and the crystal quality is optimized by utilizing the multilayer structure.
This technology enables high-quality GaN or AlN single-crystal epitaxy on AlN ceramic substrates, reducing substrate material costs, improving thermal conductivity, and lowering dislocation density, thus meeting the heat dissipation and performance requirements of devices such as 5G and HEMT.
Smart Images

Figure CN113838955B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of semiconductor material preparation, and particularly relates to a composite substrate based on aluminum nitride (AlN) ceramic material and a preparation method and application thereof. BACKGROUND
[0002] With the development of gallium nitride (GaN) material system, the application of GaN material system devices is more and more extensive. In addition to the widely used GaN-based LED devices, at present, GaN-based radio frequency devices have been widely used in the field of 5G, and GaN-based power devices, such as high electron mobility transistor (HEMT) devices, have also developed very rapidly in the field of electric vehicles and fast charging. At the same time, aluminum nitride (AlN) single crystal materials have also been widely developed and applied. The third generation of semiconductors has gradually replaced some application fields of the first and second generation of semiconductors.
[0003] In the development of GaN material devices, the substrate material has always been the basis for the development of the entire GaN material system. At present, the substrate material widely used in LED devices is sapphire substrate material. For light-emitting devices such as LEDs, sapphire substrates and patterned substrate systems have incomparable advantages in the field of GaN-based LED devices due to their excellent price advantage and long-term technical accumulation.
[0004] For GaN-based radio frequency devices and HEMT devices developed in recent years and power devices applied to 5G or electronic power, due to the pursuit of high power and high mobility, the GaN grown on sapphire has a high dislocation density, and the sapphire has poor heat dissipation performance, so the sapphire substrate cannot become the mainstream substrate for GaN-based radio frequency devices and HEMT devices. At present, the mainstream substrate used in this application field is SiC substrate or Si substrate. SiC substrate is the first choice because of its high thermal conductivity and low mismatch dislocation in material growth; and Si substrate is mainly because of its low price.
[0005] In fact, the best substrate for GaN system materials is a homoepitaxial substrate, i.e. a GaN single crystal substrate or an AlN single crystal substrate. Using a homoepitaxial substrate can greatly reduce thermal mismatch dislocations in the growth process and application process. Thermal mismatch dislocations refer to, in the case of high-temperature growth (such as the epitaxial growth temperature of GaN or AlN single crystal materials is above 1000 degrees), the thermal expansion of the substrate material and the epitaxial material is different due to different thermal expansion coefficients, and when the temperature is lowered to room temperature after the growth is completed, the shrinkage ratio of the two is significantly different, thereby causing the epitaxial material and the substrate material to accumulate a large amount of stress and dislocations caused by thermal mismatch. However, the GaN single crystal substrate or the AlN single crystal substrate belongs to the same material as the epitaxially grown GaN or AlN, and basically does not have such a thermal mismatch problem, so the quality of the grown material can be significantly improved, and this advantage is not possessed even by SiC substrates.
[0006] However, GaN single crystal substrates are very expensive and have complex preparation processes, and the global Ga resource is not sufficient, so their application in the field of power devices and the like is severely limited; and AlN single crystal substrates are also very expensive due to very complex and difficult preparation processes, and cannot be popularized. Therefore, how to maximize the use of homoepitaxial materials, i.e. GaN or AlN, while reducing the cost, has become the key to solving the problem.
[0007] Compared with AlN single crystal substrates, AlN ceramic substrates have a great cost advantage, and the cost of AlN single crystal and AlN ceramic of the same size differs by dozens of times. However, it is generally believed in the industry that although AlN ceramic material belongs to the same material as GaN or AlN material, since AlN ceramic is an amorphous or polycrystalline material, it is impossible to realize epitaxial growth of single crystal material on its surface, and thus it is impossible to use AlN ceramic material as a substrate for growing GaN or AlN single crystals. SUMMARY
[0008] The purpose of the present application is to provide a composite substrate based on AlN ceramic material for growing GaN or AlN single crystal materials and a preparation method and application thereof, which can reduce the cost of substrate materials while avoiding thermal mismatch dislocations.
[0009] Since the AlN ceramic material belongs to amorphous or polycrystalline material, how to realize the epitaxy of GaN or AlN single crystal on the surface is a huge technical gap, and is also the key that no one has tried so far. The inventor of the present application has a technical experience covering the ALN ceramic substrate, and the GaN material substrate and epitaxial technology research, is proficient in the properties of ALN ceramic substrate and the growth characteristics of sapphire substrate, and after a large number of experimental research, a composite structure of AlN ceramic substrate is accidentally developed, which can solve the problem of single crystal growth, obtain high-quality GaN and AlN epitaxial single crystal material, avoid thermal mismatch dislocation, and greatly reduce the cost of substrate material, become a great breakthrough of the whole GaN and AlN material system in the application of power devices.
[0010] The present application provides a composite substrate based on aluminum nitride ceramic material, comprising:
[0011] (a) an aluminum nitride ceramic substrate;
[0012] (b) a pattern structure layer, the pattern structure layer comprising pattern structures periodically distributed on the aluminum nitride ceramic substrate; and
[0013] (c) a polycrystalline coating layer, the polycrystalline coating layer being a continuous layer covering the pattern structure layer and the aluminum nitride ceramic substrate not covered by the pattern structure.
[0014] According to the composite substrate based on aluminum nitride ceramic material provided by the present application, the thickness of the aluminum nitride ceramic substrate can be 100-1000 μm, preferably 200-700 μm. In order to realize the growth of GaN single crystal or AlN single crystal material, the AlN ceramic substrate used in the present application is a substrate material with high-precision polished surface, and the surface roughness can be 0.01-100 nm, preferably 0.01-50 nm.
[0015] According to the composite substrate based on aluminum nitride ceramic material provided by the present application, the thickness of the pattern structure layer can be 0.01-5 μm, preferably 0.1-3.5 μm. The pattern structure layer can be composed of homogeneous material, heterogeneous material or a combination of homogeneous material and heterogeneous material of the aluminum nitride ceramic substrate. When the pattern structure layer is composed of a combination of homogeneous material and heterogeneous material of the aluminum nitride ceramic substrate, the homogeneous material is located at the bottom of the pattern structure layer, close to the aluminum nitride ceramic substrate. The thickness of the heterogeneous material and the thickness of the homogeneous material can be in any ratio. In some preferred embodiments, the ratio of the thickness of the heterogeneous material to the thickness of the homogeneous material is (0.05-0.99):(0.01-0.95), preferably (0.8-0.99):(0.01-0.2), more preferably (0.9-0.99):(0.01-0.1), for example, 0.95:0.05.
[0016] The heterogeneous material constituting the patterned structure layer can be a substrate material other than AlN commonly used in the art, for example, can be selected from one or more of SiO2, Si3N4, SiC, Si, ZnO and GaAs.
[0017] The shape of the patterned structure is not particularly limited in the present application, and can be a convex structure or a concave structure. For example, the convex structure can be selected from one or more of a cone, a cylinder, a trapezoidal round table shape, a triangular pyramid, a square pyramid, a square column, a trapezoidal square table shape, a pentagonal pyramid, a pentagonal column, a trapezoidal pentagonal table shape, a hexagonal pyramid, a hexagonal column, a trapezoidal hexagonal table shape, a 12- edge pyramid, a 12-edge column, a trapezoidal 12-edge table shape, and the like. The concave structure can be selected from one or more of a conical pit, a cylindrical pit, a trapezoidal round table pit, a triangular pyramid pit, a triangular table pit, a square pyramid pit, a square column pit, a trapezoidal square table pit, a pentagonal pyramid pit, a pentagonal column pit, a trapezoidal pentagonal table pit, a hexagonal pyramid pit, a hexagonal column pit, a trapezoidal hexagonal table pit, a 12-edge pyramid pit, a 12-edge column pit, a trapezoidal 12-edge table pit, and the like.
[0018] The period of the patterned structure (i.e., the distance between the central axes of two adjacent patterned structures, denoted by the letter A) can be 0.1-50 μm, preferably 0.2-10 μm. The base diameter of the patterned structure (denoted by the letter W) can be 0.02-50 μm, preferably 0.1-9 μm. The height of the patterned structure (denoted by the letter d) can be 0.01-5 μm, preferably 0.1-3.5 μm. Figure 1 The period and size of the patterned structure according to the present application are exemplarily shown.
[0019] The composite substrate based on aluminum nitride ceramic material according to the present application, wherein the polycrystalline coating layer can be selected from one or more of an AlN polycrystalline film, a graphene polycrystalline film, a GaN polycrystalline film, a SiC polycrystalline film, a GaAs polycrystalline film and a ZnO polycrystalline film. The polycrystalline coating layer is beneficial for the crystallization nucleation of GaN single crystal or AlN single crystal during epitaxial growth. The preferred polycrystalline coating layer is an AlN polycrystalline film and / or a graphene polycrystalline film. The thickness of the polycrystalline coating layer can be 0.01-2000 nm, preferably 1-500 nm.
[0020] The composite substrate based on aluminum nitride ceramic material according to the present application, wherein the composite substrate can further comprise:
[0021] (d) a single crystal film layer, which is an aluminum nitride single crystal layer or a gallium nitride single crystal layer covering the polycrystalline coating layer.
[0022] In this embodiment, the single crystal film layer is an AlN or GaN single crystal layer grown on the surface of the polycrystalline film layer by lateral epitaxial growth. The thickness of the single crystal film layer can vary in a wide range, for example, it can be 0.01-1000 μm, preferably 0.05-100 μm.
[0023] According to the present application, a composite substrate based on aluminum nitride ceramic material is provided, wherein, in order to further reduce the dislocation density and improve the crystal quality, the composite substrate can further comprise:
[0024] (e) a second patterned structure layer comprising a second patterned structure on the single crystal film layer, the second patterned structure being periodically and spacedly distributed on the single crystal film layer; and optionally
[0025] (f) a second polycrystalline film layer, which is a continuous layer covering the second patterned structure layer and the single crystal film layer not covered by the second patterned structure; and optionally (g) a second single crystal film layer, which is an aluminum nitride single crystal layer or a gallium nitride single crystal layer covering the second polycrystalline film layer.
[0026] Wherein, the definitions of the second patterned structure layer, the second patterned structure, the second polycrystalline film layer and the second single crystal film layer are the same as the definitions of the patterned structure layer, the patterned structure, the polycrystalline film layer and the single crystal film layer described above.
[0027] In some embodiments of the present application, in order to further reduce the dislocation density and improve the crystal quality, the composite substrate can further comprise a third patterned structure layer, and optionally a third polycrystalline film layer and a third single crystal film layer. In some embodiments of the present application, the composite substrate can further comprise a fourth patterned structure layer, and optionally a fourth polycrystalline film layer and a fourth single crystal film layer; …; an Nth patterned structure layer, and optionally an Nth polycrystalline film layer and an Nth single crystal film layer (N is any integer greater than 4). That is, after the basic structure of "aluminum nitride ceramic substrate - patterned structure layer - polycrystalline film layer - single crystal film layer" of the substrate of the present application, the patterned structure layer, the polycrystalline film layer and the single crystal film layer can be cyclically and superposedly arranged as needed, and the surface layer of the final substrate can be any one of the patterned structure layer, the polycrystalline film layer and the single crystal film layer.
[0028] The single crystal film layer and the selectively cyclically stacked pattern structure layer, polycrystal film layer and single crystal film layer are all improved by lateral epitaxial technology. The inventors have found that the crystal quality of AlN or GaN is obviously improved by one layer. However, the substrate does not have to be provided with the single crystal film layer or the cyclically stacked layers, and whether to provide the layers depends on the requirement of the application scenario of the substrate on the crystal quality of the epitaxial GaN single crystal or AlN single crystal. For the field with low requirement on the crystal quality, the single crystal film layer or the cyclically stacked layers can not be provided; for the application field with high requirement on the crystal quality, the single crystal film layer or the cyclically stacked layers can be provided as required.
[0029] The application further provides a preparation method of the composite substrate based on the aluminum nitride ceramic material, and the preparation method comprises the following steps:
[0030] (1) polishing the aluminum nitride ceramic substrate to a surface roughness of 0.01-100 nm;
[0031] (2) preparing a hetero film on the surface of the polished aluminum nitride ceramic substrate by using a film coating technology;
[0032] (3) coating a photoresist on the surface of the hetero film, exposing the photoresist to light by using a photoetching process, and etching the hetero film by using an etching process to form a pattern structure layer, wherein the pattern structure layer comprises pattern structures periodically and separately distributed on the aluminum nitride ceramic substrate;
[0033] (4) forming a polycrystal film layer on the pattern structure layer by using a film coating technology.
[0034] In a preferred embodiment, the preparation method can further comprise:
[0035] (5) growing an aluminum nitride single crystal layer or a gallium nitride single crystal layer on the surface of the polycrystal film layer by using an epitaxial growth device to form a single crystal film layer.
[0036] According to the preparation method, the step (1) can comprise: selecting a high-quality AlN ceramic substrate, polishing the surface of the AlN ceramic substrate by using a CMP (chemical mechanical polishing) technology or other polishing technologies until there is no obvious step on the surface and the roughness reaches the requirement. The thickness of the aluminum nitride ceramic substrate can be 100-1000 μm, and preferably 200-700 μm. In order to facilitate the growth of the GaN single crystal or AlN single crystal material, the AlN ceramic substrate used in the application is a high-precision polished substrate material, and the roughness is preferably 0.01-50 nm.
[0037] According to the preparation method provided by the present application, the step (2) can include: using a film plating technology such as PECVD (plasma enhanced chemical vapor deposition), CVD (chemical vapor deposition), PLD (pulsed laser deposition), etc. to prepare a hetero thin film on the surface of the AlN ceramic substrate. The hetero film can be a material such as SiO2, Si3N4, SiC, Si, ZnO, GaAs, etc. Preferably, the thickness of the hetero film is the same as or slightly greater than the thickness of the second pattern structure layer described above. For example, in some embodiments of the present application, the thickness of the hetero film can be 0.01-5 μm, preferably 0.1-3.5 μm.
[0038] According to the preparation method provided by the present application, in the step (3), a photoresist can be coated on the surface of the hetero film by using a coating process. The thickness of the photoresist depends on the required etching pattern height and the etching selectivity ratio of the hetero material and the photoresist, and the present application does not have special limitations on the thickness of the photoresist. Then, the photoresist is exposed to light to form a required pattern by using a photolithography process, such as the cylindrical, conical, cylindrical, trapezoidal circular truncated cone, triangular pyramid, square pyramid, square column, triangular square truncated cone, etc. described above. The photolithography process can use a conventional photolithography machine, a distributed exposure machine, or a nano-imprint process. Next, the hetero material on the surface of the AlN ceramic and / or part of the AlN ceramic substrate is etched into the pattern structure by using an etching process. The etching process can use dry etching or wet etching. The dry etching can use an etching process such as ICP (inductively coupled plasma etching technology) and RIE (reactive ion etching technology), and the wet etching can use a chemical reagent corrosion method, such as an acid, alkali, or organic reagent, etc.
[0039] According to the preparation method provided by the present application, in the step (4), a homo or hetero polycrystalline film is plated on the pattern structure layer formed in the step (3) by using a film plating technology. The polycrystalline film can be one or more of AlN polycrystalline film, graphene polycrystalline film, GaN polycrystalline film, SiC polycrystalline film, GaAs polycrystalline film, and ZnO polycrystalline film. The film plating process can select one or more of PVD (physical vapor deposition), MOCVD (metal organic chemical vapor deposition), HVPE (hydride vapor phase epitaxy), MBE (molecular beam epitaxy), and PLD (pulsed laser deposition), etc.
[0040] According to the preparation method provided by the present application, in the step (5), a GaN or AlN single crystal thin film is laterally epitaxially grown on the surface of the polycrystalline film layer by using an epitaxial growth device. The epitaxial growth can use various growth methods such as MOCVD, HVPE, PLD, and PVD, preferably MOCVD and HVPE. The growth technology can refer to the known GaN or AlN single crystal epitaxial growth technology.
[0041] In some embodiments of the present application, in order to further reduce the dislocation density and improve the crystal quality, the preparation can further comprise: repeating one or more steps of steps (2) to (5) after step (5) to further form a second patterned structure layer, and optionally a second polycrystalline coating layer and an optional second single crystal film layer; further optionally a third patterned structure layer, a third polycrystalline coating layer and a third single crystal film layer; further optionally a fourth patterned structure layer, a fourth polycrystalline coating layer and a fourth single crystal film layer;...; and optionally an Nth patterned structure layer, an Nth polycrystalline coating layer and an Nth single crystal film layer (N is any integer greater than 4). That is, after the basic structure of "AlN ceramic substrate - patterned structure layer - polycrystalline coating layer - single crystal film layer" of the substrate of the present application, the patterned structure layer, the polycrystalline coating layer and the single crystal film layer can be stacked as needed, and the surface layer of the final substrate can be any one of the patterned structure layer, the polycrystalline coating layer and the single crystal film layer.
[0042] The present application also provides the use of the AlN ceramic material-based composite substrate or the AlN ceramic material-based composite substrate prepared by the method of the present application in the epitaxial growth of GaN or AlN single crystal materials.
[0043] The beneficial effects and technical breakthroughs of the present application over the prior art are:
[0044] (I) The use of the first three layers solves the biggest technical problem of growing GaN or AlN single crystals on AlN ceramic substrates, which are non-crystalline substrates. The presence of the second and third layers solves the problem of epitaxial growth of single crystal GaN or AlN on non-single crystal AlN ceramic substrates. Using the method provided by the present application, unexpected epitaxial effects are achieved, breaking through the original concept. The original thinking and experimental law believes that it is impossible to break through the growth of single crystal structure on non-single crystal substrates. The present application breaks through the inherent thinking and successfully realizes the growth of GaN or AlN single crystal materials on AlN ceramic substrates.
[0045] (II) The substrate of the present application has obvious advantages compared with the existing SiC substrate. The cost of the SiC substrate and the substrate of the present application of the same size can differ by 10 times. The substrate of the present application has the advantages of using homoepitaxy, significantly reducing dislocation density, reducing growth difficulty, and having obvious thermal conductivity advantage. First, the present application utilizes the high heat dissipation performance of the AlN ceramic substrate. The theoretical thermal conductivity of the AlN ceramic substrate can reach 320 W / mk. The current AlN ceramic substrate can reach more than 180 W / mk, which has obvious improvement compared with the thermal conductivity of 100 W / mk of the Si substrate. The thermal conductivity of the SiC substrate on the market is mostly between 120-150 W / mk. The composite substrate of the present application has obvious advantages and can meet the heat dissipation requirements of the current 5G or HEMT GaN or AlN power device. Second, the AlN ceramic composite substrate of the present application and the AlN single crystal or GaN single crystal epitaxially grown thereon belong to the same material, and the thermal mismatch between the two is almost zero, which has obvious advantages for improving the crystal quality of epitaxial GaN or AlN. Third, the fourth layer of the composite substrate of the present application is a GaN or AlN single crystal layer. Such a composite substrate basically realizes homoepitaxy when GaN or AlN is epitaxied, which has great advantages compared with SiC substrate or Si substrate.
[0046] (III) In the preferred embodiment of the present application, the fourth layer of AlN or GaN single crystal film is set to further improve the crystal quality, so that high-quality GaN single crystal or AlN single crystal can be homoepitaxially grown on the composite substrate of the present application.
[0047] (IV) The composite substrate of the present application has simple preparation process and obvious price advantage compared with GaN single crystal substrate or AlN single crystal substrate. The cost of the GaN single crystal substrate or AlN single crystal substrate of the same size is 10 to 20 times or more than that of the substrate of the present application. BRIEF DESCRIPTION OF DRAWINGS
[0048] The embodiments of the present application will be described in detail below in conjunction with the drawings, in which:
[0049] Figure 1 It is a schematic view of the period and size of the pattern structure of the composite substrate of the present application.
[0050] Figure 2 It is an SEM image of the pattern structure layer formed in step (3) of Example 1 of the present application.
[0051] Figure 3 It is an SEM photo of the surface of GaN with a thickness of 2 microns grown by MOCVD in step (5) of Example 1 of the present application.
[0052] Figure 4SEM photograph of the surface of GaN with a thickness of 4 microns grown by MOCVD in step (5) of Example 1 of the present application;
[0053] Figure 5 XRD pattern of the GaN single crystal layer on the surface of the composite substrate prepared in Example 1 of the present application;
[0054] Figure 6 XRD pattern of the GaN single crystal layer on the surface of the composite substrate prepared in Example 2 of the present application;
[0055] Figure 7 SEM photograph of the surface of the composite substrate prepared in Example 3 of the present application;
[0056] Figure 8 SEM photograph of the surface of the composite substrate prepared in Example 4 of the present application;
[0057] Figure 9 SEM photograph of the surface of the composite substrate prepared in Example 5 of the present application;
[0058] Figure 10 SEM photograph of the cross section of the GaN single crystal grown on the surface of the composite substrate prepared in Example 6 of the present application;
[0059] Figure 11 SEM photograph of the surface of the composite substrate prepared in Example 7 of the present application;
[0060] Figure 12 Photograph of the back surface of the substrate prepared in Comparative Example 1 taken by a high power microscope. DETAILED DESCRIPTION
[0061] The present application will be further described in conjunction with the specific embodiments given below, which are only intended to illustrate the present application, but not to limit the scope of the present application.
[0062] Example 1
[0063] This example is used to illustrate the composite substrate of the present application and the method for preparing the same.
[0064] (1) A high quality AlN ceramic substrate (Zhongchuanyanyuan Semiconductor Technology Co., Ltd., 180 W / mk aluminum nitride ceramic substrate) with a thickness of 500 microns was selected, and the surface of the AlN ceramic substrate was polished by CMP polishing method. The microscope showed that the surface had no obvious steps, and the surface roughness was within 25 nm;
[0065] (2) A SiO2 thin film was grown on the polished surface of the above ceramic substrate by PECVD technology, and the thickness of the SiO2 thin film was 2.0 microns;
[0066] (3) using a glue spreader to coat the SiO2 surface with photoresist having a thickness of 1.2 microns, using nano-imprint technology to imprint the photoresist into a periodic cylinder having a base diameter of 2 microns, a height of about 2.4 microns, and a period of 3 microns; using ICP etching technology to etch the AlN ceramic substrate after imprinting, and etching the SiO2 film on the ceramic substrate into a circular truncated cone pattern. The circular truncated cone pattern has a base diameter of 2.8 microns, a height of 1.8 microns, and a period of 3 microns, and is uniformly arranged on the AlN ceramic surface. The upper part of the circular truncated cone pattern is SiO2, and the lower part is AlN ceramic. The height ratio of SiO2 to AlN ceramic is 0.95:0.05. The area of the AlN ceramic surface without the pattern is exposed after etching, i.e., the area without the pattern has no SiO2 on the surface, and the AlN ceramic surface is exposed;
[0067] (4) using PVD technology to coat the patterned AlN ceramic substrate with a 15-nm-thick AlN polycrystalline film, so as to cover the patterned and non-patterned areas;
[0068] (5) using MOCVD technology to epitaxially grow a GaN film on the patterned AlN ceramic substrate coated with the AlN polycrystalline film, and using lateral epitaxial technology to grow a single-crystal GaN film having a thickness of 4 microns, thereby obtaining the composite substrate of the present application.
[0069] Figure 2 SEM image of the patterned structure layer formed in step (3) of the present embodiment.
[0070] Figure 3 SEM image of the surface of the GaN layer having a thickness of 2 microns grown by MOCVD in step (5) of the present embodiment. It can be seen that the patterned area is not completely closed. Figure 4 SEM image of the surface of the GaN layer having a thickness of 4 microns grown by MOCVD in step (5) of the present embodiment. It can be seen that the GaN surface is completely closed, and the growth quality is very high.
[0071] Figure 5 XRD pattern of the GaN single-crystal layer on the surface of the composite substrate prepared in the present embodiment. The pattern can reflect the GaN crystal quality of the composite substrate. According to the XRD test results, the dislocation density of the GaN crystal prepared in the present embodiment is calculated to be 7.3×10 8 , and the crystal quality is very good. On the basis of this substrate, the GaN single crystal or AlN single crystal epitaxially grown in the application process will have a crystal quality not lower than that of the GaN film layer after step (5), and can be perfectly applied in the application field.
[0072] Example 2
[0073] The present embodiment is used to illustrate the composite substrate and the preparation method thereof.
[0074] (1) Select high-quality AlN ceramic substrate (Zhongchuanyanyuan Semiconductor Technology Co., Ltd. 180W / mk aluminum nitride ceramic substrate) with a thickness of 500 microns, polish the surface of the AlN ceramic substrate using CMP polishing method, the microscope shows that the surface has no obvious step, and the surface roughness is within 5nm;
[0075] (2) Grow SiO2 film on the polished surface of the above ceramic substrate using PECVD technology, the thickness of the SiO2 film is 1.5 microns;
[0076] (3) Use a glue applicator to apply photoresist with a thickness of 1.2 microns on the above SiO2 surface, use nano-imprinting technology to imprint the photoresist into a periodic cylinder with a bottom diameter of 2μm, a height of about 2.4μm, and a period of 3μm; use ICP etching technology to etch the AlN ceramic substrate after imprinting, etch the SiO2 film on the surface of the ceramic substrate into a circular truncated cone pattern. The circular truncated cone pattern has a bottom diameter of 2.8μm, a height of 1.5μm, and a period of 3μm, and is uniformly arranged on the AlN ceramic surface. The upper part of the circular truncated cone pattern is SiO2, and the lower part is AlN ceramic. The height ratio of SiO2 and AlN ceramic material is 0.8:0.2. The area of the AlN ceramic surface without pattern is exposed after etching, i.e. the area without pattern has no SiO2 on the surface, and the AlN ceramic surface is exposed;
[0077] (4) Use PVD technology to coat an AlN polycrystalline film with a thickness of 40nm on the surface of the above AlN ceramic patterned substrate, covering the patterned and non-patterned areas;
[0078] (5) Use MOCVD technology to epitaxially grow GaN film on the patterned AlN ceramic substrate coated with AlN polycrystalline film, use lateral epitaxy technology to grow single crystal GaN film, and the film thickness is 2 microns.
[0079] (6) Grow SiO2 film on the surface of the GaN single crystal film grown in step (5) using PECVD technology, and the thickness of the SiO2 film is 2.0 microns;
[0080] (7) using a glue spreader to coat the SiO2 surface with photoresist with a thickness of 1.2 microns, using nanoimprint technology to imprint the photoresist into a periodic cylinder with a base diameter of 2 microns, a height of about 2.4 microns, and a period of 3 microns; using ICP etching technology to etch the AlN ceramic substrate after imprinting, and etching the SiO2 film on the surface of the ceramic substrate into a conical pattern. The conical pattern has a base diameter of 2.8 microns, a height of 1.8 microns, and a period of 3 microns, and is uniformly arranged on the surface of the GaN single crystal film. The upper part of the conical pattern is SiO2, and the lower part is GaN single crystal. The height ratio of SiO2 and GaN single crystal is 0.5:0.5. The area of the GaN single crystal film surface without patterns is exposed after etching, i.e. the surface of the area without patterns is free of SiO2, and the GaN single crystal film surface is exposed;
[0081] (8) using PVD technology to coat the surface of the GaN single crystal film patterned substrate with a 20 nm thick AlN polycrystalline film, covering the patterned and non-patterned areas;
[0082] (9) using HVPE technology to epitaxially grow GaN film on the patterned AlN ceramic substrate coated with AlN polycrystalline film, using lateral epitaxy technology to grow single crystal GaN film, with a film thickness of 40 microns, thereby obtaining the composite substrate of the present application.
[0083] Figure 6 The XRD pattern of the GaN single crystal layer on the surface of the composite substrate prepared in this embodiment is shown. After two cycles of patterned structure, the GaN single crystal dislocation density is reduced to 5.1 x 10 7 After the second lateral epitaxy, the crystal quality is significantly improved. On the basis of this substrate, the GaN single crystal or AlN single crystal epitaxially grown in the application process will have a crystal quality not lower than that of the GaN film grown in step (9), and can be perfectly applied in the field of power devices.
[0084] Example 3
[0085] This embodiment is used to illustrate the composite substrate and the preparation method thereof.
[0086] (1) A high-quality AlN ceramic substrate (Japan Maruwa Co., Ltd. 180W / mk aluminum nitride ceramic substrate) with a thickness of 200 microns is selected, and the surface of the AlN ceramic substrate is polished using CMP polishing method. The microscope shows that the surface has no obvious steps, and the surface roughness is within 0.01 nm;
[0087] (2) SiO2 film is grown on the polished surface of the ceramic substrate using PECVD technology, and the thickness of the SiO2 film is 1.5 microns;
[0088] (3) A spin coater is used to coat a photoresist with a thickness of 1.2 microns on the surface of the SiO2, and a nano-imprint technique is used to imprint the photoresist into a periodic cylinder with a bottom diameter of 2 microns, a height of about 2.4 microns, and a period of 3 microns; an ICP etching technique is used to etch the AlN ceramic substrate after imprinting, and the SiO2 film on the surface of the ceramic substrate is etched into a circular truncated cone pattern. The circular truncated cone pattern has a bottom diameter of 2.8 microns, a height of 1.5 microns, and a period of 3 microns, and is uniformly arranged on the surface of the AlN ceramic. The upper part of the circular truncated cone pattern is SiO2, and the lower part is AlN ceramic. The height ratio of SiO2 and AlN ceramic is 0.9:0.1. The area without pattern on the surface of the AlN ceramic is exposed after etching, i.e., the area without pattern has no SiO2 on the surface, and the AlN ceramic surface is exposed;
[0089] (4) A PVD technique is used to plate an AlN polycrystalline film with a thickness of 40 nm on the surface of the AlN ceramic patterned substrate, so as to cover the patterned and non-patterned areas;
[0090] (5) A MOCVD technique is used to epitaxially grow a GaN film on the patterned AlN ceramic substrate with the plated AlN polycrystalline film. A lateral epitaxial technique is used to grow a single-crystal GaN film, and the film layer has a thickness of 4 microns.
[0091] (6) A PECVD technique is used to grow a SiO2 film on the surface of the GaN single-crystal film layer grown in the step (5), and the SiO2 film has a thickness of 2.0 microns;
[0092] (7) A spin coater is used to coat a photoresist with a thickness of 1.2 microns on the surface of the SiO2, and a nano-imprint technique is used to imprint the photoresist into a periodic cylinder with a bottom diameter of 2 microns, a height of about 2.4 microns, and a period of 3 microns; an ICP etching technique is used to etch the AlN ceramic substrate after imprinting, and the SiO2 film on the surface of the ceramic substrate is etched into a circular truncated cone pattern. The circular truncated cone pattern has a bottom diameter of 2.8 microns, a height of 1.5 microns, and a period of 3 microns, and is uniformly arranged on the surface of the AlN ceramic. The upper part of the circular truncated cone pattern is SiO2, and the lower part is AlN ceramic. The height ratio of SiO2 and AlN ceramic is 0.9:0.1. The area without pattern on the surface of the AlN ceramic is exposed after etching, i.e., the area without pattern has no SiO2 on the surface, and the AlN ceramic surface is exposed.
[0093] Figure 7 The SEM image of the surface of the composite substrate prepared in this embodiment can be seen to have uniform pattern arrangement. According to the XRD test result, it is calculated that the dislocation density of the GaN single crystal grown on the composite substrate prepared in this embodiment is about 10 7 microns.
[0094] Example 4
[0095] This embodiment is used to illustrate the composite substrate and the preparation method thereof.
[0096] (1) A high-quality AlN ceramic substrate (Nippon Yushi Co., Ltd. 180W / mk aluminum nitride ceramic substrate) with a thickness of 1000 microns is selected, and the surface of the AlN ceramic substrate is polished by using a CMP polishing method. The microscope shows that the surface has no obvious steps, and the surface roughness is within 50 nm;
[0097] (2) A Si3N4 thin film with a thickness of 1.5 microns is grown on the polished surface of the ceramic substrate by using a PECVD technology;
[0098] (3) A photoresist with a thickness of 1.2 microns is coated on the surface of the Si3N4 by using a glue coating machine, and the photoresist is imprinted into a periodic cylinder with a bottom diameter of 2 microns, a height of about 2.4 microns, and a period of 3 microns by using a nano-imprinting technology. The Si3N4 thin film on the surface of the ceramic substrate is etched into a conical pattern by using an ICP etching technology. The conical pattern has a bottom diameter of 2.8 microns, a height of 1.5 microns, and a period of 3 microns, and is uniformly arranged on the surface of the AlN ceramic. The upper part of the conical pattern is Si3N4, and the lower part is AlN ceramic. The height ratio of Si3N4 and AlN ceramic is 0.85:0.15. The areas without patterns on the surface of the AlN ceramic are exposed after etching, i.e., the areas without patterns do not have Si3N4, and the AlN ceramic surface is exposed;
[0099] (4) A polycrystalline AlN thin film with a thickness of 100 nm is plated on the surface of the AlN ceramic patterned substrate by using a PVD technology, so that the patterned and non-patterned areas are completely covered, i.e., a composite substrate of the present application is obtained.
[0100] Figure 8 The SEM image of the surface of the composite substrate prepared in this embodiment can be seen. According to the XRD test results, the dislocation density of the GaN single crystal grown on the composite substrate prepared in this embodiment is calculated to be about 10 8 .
[0101] Example 5
[0102] This embodiment is used to illustrate the composite substrate and the preparation method thereof.
[0103] (1) A high-quality AlN ceramic substrate (Nippon Yushi Co., Ltd. 180W / mk aluminum nitride ceramic substrate) with a thickness of 1000 microns is selected, and the surface of the AlN ceramic substrate is polished by using a CMP polishing method. The microscope shows that the surface has no obvious steps, and the surface roughness is within 50 nm;
[0104] (2) Utilize PECVD technology to grow SiO2 film on the polished surface of the ceramic substrate, and the thickness of the SiO2 film is 1.8 microns;
[0105] (3) Utilize a glue coating machine to coat photoresist with a thickness of 1.2 microns on the surface of the SiO2, utilize nano-imprinting technology to imprint the photoresist into a periodic cylinder with a bottom diameter of 2 microns, a height of about 2.4 microns, and a period of 3 microns; utilize ICP etching technology to etch the AlN ceramic substrate after imprinting, and etch the SiO2 film on the surface of the ceramic substrate into a conical pattern. The conical pattern has a bottom diameter of 2.8 microns, a height of 1.7 microns, and a period of 3 microns, and is uniformly arranged on the surface of the AlN ceramic. The upper part of the conical pattern is SiO2, and the lower part is AlN ceramic. The height ratio of SiO2 and AlN ceramic material is 0.95:0.05. The area without pattern on the surface of the AlN ceramic is exposed after etching, i.e., the area without pattern has no SiO2 on the surface, and the AlN ceramic surface is exposed;
[0106] (4) Utilize PVD technology to plate a graphene polycrystal film with a thickness of 300 nm on the surface of the AlN ceramic patterned substrate, so as to cover the patterned and non-patterned areas, i.e., to obtain the composite substrate of the application.
[0107] Figure 9 The SEM image of the surface of the composite substrate prepared in this embodiment can be seen to have uniform pattern arrangement. According to the XRD test results, the dislocation density of the GaN single crystal grown on the composite substrate prepared in this embodiment is calculated to be about 10 8 , which meets the application requirements.
[0108] Example 6
[0109] This embodiment is used to illustrate the composite substrate and the preparation method thereof.
[0110] (1) Select a high-quality AlN ceramic substrate with a thickness of 430 microns (180W / mk aluminum nitride ceramic substrate of Zhongchuanyanyuan Semiconductor Technology Co., Ltd.), polish the surface of the AlN ceramic substrate by utilizing CMP polishing, and the microscope shows that the surface has no obvious steps, and the surface roughness is within 5 nm;
[0111] (2) Utilize PECVD technology to grow SiO2 film on the polished surface of the ceramic substrate, and the thickness of the SiO2 film is 200 nanometers;
[0112] (3) using a glue spreader to coat the SiO2 surface with photoresist with a thickness of 500 nm, using nanoimprint technology to imprint the photoresist into a periodic cylinder with a bottom diameter of 400 nm, a height of about 700 nm, and a period of 500 nm; using wet etching technology, specifically using BOE etching solution, soaking the sample for 40 seconds at room temperature, then using acetone alcohol to remove the residual photoresist, and then using deionized water to clean, wet etching the SiO2 film on the surface of the ceramic substrate into a circular cone shape. The bottom diameter of the circular cone pattern is about 450 nm, the height is about 150 nm, and the period is 500 nm. The circular cone pattern material is uniformly arranged on the surface of the AlN ceramic, and the upper part of the circular cone pattern material is SiO2 and the lower part is AlN ceramic. The height ratio of SiO2 and AlN ceramic material is 0.8:0.2. The area of the AlN ceramic surface without patterns is exposed after etching, i.e. the area without patterns has no SiO2 on the surface, and the AlN ceramic surface is exposed;
[0113] (4) using PVD technology to coat the AlN ceramic patterned substrate surface with a 3 nm thick AlN polycrystalline film, covering the entire patterned and non-patterned area, i.e. obtaining the composite substrate of the present application.
[0114] Figure 10 The cross-sectional SEM image of the composite substrate prepared in this embodiment after growing GaN single crystal on the surface of the composite substrate can be seen. The pattern period is about 500 nm, and the height is about 150 nm. According to the XRD test results, the composite substrate prepared in this embodiment is used for growing GaN single crystal, and the crystal dislocation density can reach 10 8 nm or less.
[0115] Example 7
[0116] This embodiment is used to illustrate the composite substrate and the preparation method thereof.
[0117] (1) Select a high-quality AlN ceramic substrate with a thickness of 500 microns (Japan Maruwa Corporation 180W / mk aluminum nitride ceramic substrate), polish the surface of the AlN ceramic substrate using CMP polishing, and the microscope shows that the surface has no obvious steps, and the surface roughness is within 10 nm;
[0118] (2) using PECVD technology to grow a SiO2 film on the polished surface of the ceramic substrate, the SiO2 film has a thickness of 1 micron;
[0119] (3) using a glue spreader to coat the SiO2 surface with photoresist with a thickness of 1.7 microns, using nanoimprint technology to imprint the photoresist into a periodic triangular pyramid with a base diameter of 2.5 microns, a height of about 3.4 microns, and a period of 5 microns; using ICP etching technology to etch the AlN ceramic substrate after imprinting, and etching the SiO2 film on the surface of the ceramic substrate into a triangular pyramid pattern. The base diameter of the conical pattern is 2.8 microns, the height is 3 microns, and the period is 5 microns, and the triangular pyramid pattern material is uniformly arranged on the surface of the AlN ceramic, the upper part of the triangular pyramid pattern material is SiO2, and the lower part is AlN ceramic, and the height ratio of SiO2 and AlN ceramic material is 0.05:0.95. The area without pattern on the surface of the AlN ceramic is exposed after etching, i.e. the area without pattern has no SiO2 on the surface, and the AlN ceramic surface is exposed;
[0120] (4) using PVD technology to coat a graphene polycrystalline film with a thickness of 40 nm on the surface of the AlN ceramic patterned substrate, covering the patterned and non-patterned areas, i.e. obtaining the composite substrate of the application.
[0121] Figure 11 The SEM image of the surface of the composite substrate prepared in this embodiment. According to the XRD test results, the composite substrate prepared in this embodiment is good for growing GaN single crystals, and the crystal dislocation density can reach 10 9 around.
[0122] The focus of the application is to break through the technical difficulties of growing GaN single crystals or AlN single crystals on traditional AlN ceramic substrates, which are amorphous materials or polycrystalline materials.
[0123] The inventor of the present application disclosed a method for growing GaN single crystals on near-single-crystal AlN ceramic substrates in the previous patent application, and the present application is clearly different from the previous invention.
[0124] The main type of AlN ceramic substrate is amorphous or polycrystalline material, and the preparation process of the near-single-crystal AlN ceramic substrate with a similar c-axis orientation is very complex, and the preparation cost is 3-5 times higher than that of general AlN ceramic substrates.
[0125] In order to show the effectiveness of the pattern structure of the present application for growing GaN or AlN single crystals on ordinary amorphous or polycrystalline AlN ceramic substrates, the following comparative examples are carried out.
[0126] Comparative Example 1
[0127] The preparation steps are as follows:
[0128] (1) Select high-quality AlN ceramic substrate (Zhongchuanyanyuan Semiconductor Technology Co., Ltd. 180W / mk aluminum nitride ceramic substrate) with a thickness of 500 microns, polish the surface of the AlN ceramic substrate using CMP polishing method, the microscope shows that the surface has no obvious step, and the surface roughness is within 25 nm;
[0129] (2) Grow SiO2 film on the polished surface of the ceramic substrate using PECVD technology, the thickness of the SiO2 film is 1.5 microns;
[0130] (3) Use a glue applicator to apply photoresist with a thickness of 1.2 microns on the SiO2 surface, and use nano-imprinting technology to imprint the photoresist into a periodic cylinder with a base diameter of 2 μm, a height of about 2.4 μm, and a period of 3 μm;
[0131] In this comparative example, the periodic cylinder pattern is not uniformly distributed on the AlN ceramic surface, but some areas have periodic patterns and some areas do not. The SiO2 film on the surface of the ceramic substrate is etched into a truncated cone pattern using ICP etching technology. The base diameter of the truncated cone pattern is 2.8 μm, the height is 1.5 μm, and the period is 3 μm.
[0132] The periodic truncated cone pattern is not uniformly distributed on the AlN ceramic surface, but some areas have periodic patterns and some areas do not. The upper part of the truncated cone pattern is SiO2 and the lower part is AlN ceramic, and the height ratio of SiO2 and AlN ceramic material is 0.95:0.05. The area without pattern on the AlN ceramic surface is exposed after etching, i.e. the area without pattern has no SiO2 on the surface, and the AlN ceramic surface is exposed;
[0133] (4) Use PVD technology to plate a 15 nm thick AlN polycrystalline film on the surface of the AlN ceramic patterned substrate, covering the patterned and non-patterned areas;
[0134] (5) Use MOCVD technology to epitaxially grow GaN film on the patterned AlN ceramic substrate with plated AlN polycrystalline film, use lateral epitaxy technology to grow single crystal GaN film, and the film thickness is 4 microns.
[0135] Figure 12For the experimental results of the above-mentioned comparative example, a detail photo of the back surface of the sample after growing GaN was observed by a high-power microscope, the circle area at the lower left of the photo was a patterned area, and the circle area at the upper right of the photo was a non-patterned area. It can be seen from the detail photo of the back surface of the sample after growing GaN that, in the patterned area, GaN grows continuously and forms a single crystal; while in the non-patterned area, GaN grows in disorder and is non-single crystal. This result fully proves the effectiveness of the present application for overcoming the amorphous substrate or polycrystalline substrate of the common AlN ceramic substrate to epitaxially grow GaN or AlN single crystal. It makes it independent of the crystal direction structure of the substrate.
Claims
1. A composite substrate based on aluminum nitride ceramic material for epitaxial growth of GaN or AlN single crystals, comprising: (a) An aluminum nitride ceramic substrate with a surface roughness of 0.01-100 nm; (b) A patterned structure layer, the patterned structure layer comprising patterned structures periodically spaced on the aluminum nitride ceramic substrate; and (c) A polycrystalline coating layer, wherein the polycrystalline coating layer is a continuous layer covering the patterned structure layer and the aluminum nitride ceramic substrate not covered by the patterned structure. The patterned structure layer is composed of a combination of homogeneous and heterogeneous materials of an aluminum nitride ceramic substrate, wherein the heterogeneous material is selected from one or more of SiO2, Si3N4, SiC, Si, ZnO and GaAs. The thickness of the patterned structure layer is 0.1-3.5 μm, the ratio of the thickness of the heterogeneous material to the thickness of the homogeneous material is (0.9-0.99):(0.01-0.1), the period of the patterned structure is 0.2-10 μm, the bottom diameter of the patterned structure is 0.1-9 μm, the height of the patterned structure is 0.1-3.5 micrometers, and the thickness of the polycrystalline coating layer is 1-500 nm.
2. The composite substrate based on aluminum nitride ceramic material according to claim 1, wherein, The thickness of the aluminum nitride ceramic substrate is 100-1000 μm.
3. The composite substrate based on aluminum nitride ceramic material according to claim 1, wherein, The thickness of the aluminum nitride ceramic substrate is 200-700 μm.
4. The composite substrate based on aluminum nitride ceramic material according to claim 1, wherein, The surface roughness of the aluminum nitride ceramic substrate is 0.01-50 nm.
5. The composite substrate based on aluminum nitride ceramic material according to claim 1, wherein, The polycrystalline coating layer is selected from one or more of AlN polycrystalline film, graphene polycrystalline film, GaN polycrystalline film, SiC polycrystalline film, GaAs polycrystalline film and ZnO polycrystalline film.
6. The composite substrate based on aluminum nitride ceramic material according to claim 5, wherein, The polycrystalline coating layer is an AlN polycrystalline film and / or a graphene polycrystalline film.
7. The composite substrate based on aluminum nitride ceramic material according to any one of claims 1 to 6, wherein, The composite substrate further includes: (d) Single crystal film layer, wherein the single crystal film layer is an aluminum nitride single crystal layer or a gallium nitride single crystal layer covering the polycrystalline coating layer.
8. The composite substrate based on aluminum nitride ceramic material according to claim 7, wherein, The thickness of the single-crystal film is 0.01-1000 μm.
9. The composite substrate based on aluminum nitride ceramic material according to claim 8, wherein, The thickness of the single-crystal film is 0.05-100 μm.
10. The composite substrate based on aluminum nitride ceramic material according to claim 7, wherein, The composite substrate further includes: (e) A second patterned structure layer, the second patterned structure layer including a second patterned structure located on the monocrystalline film layer, the second patterned structure being periodically spaced on the monocrystalline film layer; (f) A second polycrystalline coating layer, wherein the second polycrystalline coating layer is a continuous layer covering the second patterned structure layer and the monocrystalline film layer not covered by the second patterned structure; (g) A second single-crystal film layer, wherein the second single-crystal film layer is an aluminum nitride single-crystal layer or a gallium nitride single-crystal layer covering the second polycrystalline coating layer.
11. A method for preparing a composite substrate based on aluminum nitride ceramic material according to any one of claims 1 to 10, the method comprising the following steps: (1) Polish the aluminum nitride ceramic substrate until the surface roughness is 0.01-100 nm; (2) A heterogeneous film is prepared on the surface of a polished aluminum nitride ceramic substrate using a coating technique; (3) Photoresist is coated on the surface of the heterogeneous film, and the photoresist is exposed into a pattern using a photolithography process. Then, the heterogeneous film and part of the aluminum nitride ceramic substrate on the surface of the aluminum nitride ceramic substrate are etched using an etching process to form a pattern structure layer. The pattern structure layer includes pattern structures that are periodically spaced on the aluminum nitride ceramic substrate. (4) A polycrystalline coating layer is formed on the patterned structure layer using coating technology.
12. The preparation method according to claim 11, wherein, The preparation method further includes: (5) Using an epitaxial growth device, an aluminum nitride single crystal layer or a gallium nitride single crystal layer is grown on the surface of the polycrystalline coating layer to form a single crystal film layer.
13. The application of the composite substrate based on aluminum nitride ceramic material according to any one of claims 1 to 10, or the composite substrate based on aluminum nitride ceramic material prepared according to the preparation method according to claim 11 or 12, in the epitaxial growth of GaN single crystal or AlN single crystal materials.
Citation Information
Patent Citations
Gallium nitride-based chip with ceramic substrate and manufacturing method
CN102456721A
Method for forming group iii nitride semiconductor layer, method for manufacturing group iii nitride semiconductor substrate, and group iii nitride semiconductor substrate
JP2006315895A
Gallium nitride-on-silicon interface
US20080280426A1
Method for producing group iii nitride semiconductor layer, group iii nitride semiconductor light-emitting device, and lamp
US20100025684A1